2002
DOI: 10.2134/agronj2002.0023
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality

Abstract: The term soil quality (SQ) encompasses both a soil's productive and environmental capabilities. Strategies or frameworks that help farmers manage SQ are vital as sole emphasis on production can have negative environmental consequences and exclusive focus on environmental considerations could endanger supplies of food or fiber. Recent efforts in the USA have prioritized the development of SQ assessment strategies that would be used by individual farmers. The Illinois Soil Quality Initiative (ISQI) is an example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Another reason could be that no purification concepts exist for soil science (Warkentin and Fletcher, 1977). As opposed to water quality/health, no "pure" natural soil can be found that could be used as a reference or standard measured by certain chemical concentrations.…”
Section: Criteria For Indicator/index Developmentmentioning
confidence: 99%
“…Another reason could be that no purification concepts exist for soil science (Warkentin and Fletcher, 1977). As opposed to water quality/health, no "pure" natural soil can be found that could be used as a reference or standard measured by certain chemical concentrations.…”
Section: Criteria For Indicator/index Developmentmentioning
confidence: 99%
“…The score of these indicators was then derived by dividing the corresponding observed value by the highest value. For the available P value, where higher was better up to the optimum value of 50 kg ha"' (Wander et al, 2002) and thereafter less was better, scores were derived by dividing the observed values <50 kg ha"' by 50, and for observed values >50 kgha" , scores were determined by dividing 50 by the observed values. For available Zn values below 0.6 mg kg" , the observed values were divided by 0.6 and those above 0.6 mg kg" ' were assigned a score of 1 .…”
Section: Soil Quality Index Calculation and Interpretationmentioning
confidence: 99%
“…A requirement for the design of a SQ management and assessment framework (SQMAF) involves the identification of a set of minimum, quantitative, and readily available data that represent the soil functions of interest (Carter, 2002; Arshad and Martin, 2002; Doran and Parkin, 1994; Wander et al, 2002). This includes parameters showing measurable responses to changes in management, climate, and edaphic factors (Andrews et al, 2004; Doran and Parkin, 1994; Doran and Parkin, 1996).…”
mentioning
confidence: 99%